STRATEGI KOMUNIKASI HUMAS BMKG DALAM EDUKASI RISIKO BENCANA GEMPA MEGATHRUST DI MEDIA SOSIAL - Nur Septiana Embisa, Rully; Tri Harpin Pranata, Rici (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Social media have pushed government organizations to use them as a tool for public education on calamities and for spreading correct information on megathrust challenges. This creative approach combines the roles of public relations as a communication intermediary with the geophysics department by means of a visual and captivating approach for communicating risk. The qualitative method involvels using a case study approach that includes detailed interviews, observations, and data collection. Along with followers of the BMKG social media channels, the group of informants included people from the geophysics department, Instagram managers, public relations staff. Together with a four-phase public relations approach, the study of the data used the framework created by Miles, Huberman, and Saldana. Findings show that BMKG includes framing techniques about megathrust into its communication plans to increase public involvement as well as uses social media to tackle issues connected to false information and megathrust. The risk communication method was determined to have changed toward digital, flexible, graphic, and participative.